Subantance Use Among Third year Medical Students of Nepal - Budhathoki, N; Shrestha, M K; Acharya, N; Manandhar, A (Journal of Nepal Health Research Council, 2010)
Background: Substance use is very rampant in a developing country like Nepal. Unfortunately, medical field is not exempt from it either. Substance use among medical students and doctors not only reduces their efficiency at present but also increases their DALY on long term. The main objectives of the study were to assess the prevalence of substance use among medical student and to find out whether substance use started before or after joining the Medical school. Methods: The study design employed for the research was descriptive cross sectional. A structured questionnaire about current use of tobacco, alcohol and marijuana was used to collect the data from third year students from eight medical and one dental college from across the country having 2006 batch. Results: The overall response rate was 74.12% (N=510). Among those who responded, prevalence of substance use was 49.6%, of which 38.2% were Nepalese nationals and 11.4% were foreign nationals and 39% were male and 10.6% female. Alcohol based product users were 52.3%, tobacco based product users were 55% and marijuana users were 65.7% and all started using them after joining the medical school. Conclusions: Almost half of the respondents were involved in some sort of substance use and more than half of those using started after joining medical school. Hence if proper measures are taken to address this then its prevalence can be significantly reduced if not eliminated completely. Key words: cross sectional study,prevalence, substance use